Rapid response in recovery time, humidity sensing behavior and magnetic properties of rare earth(Dy & Ho) doped Mn–Zn ceramics. Issue 20 (15th October 2021) - El-Denglawey, A.; Manjunatha, K.; Vijay Sekhar, E.; Chethan, B.; Zhuang, Jian; Angadi V, Jagadeesha
Abstract: In the present world, the development of room temperature humidity sensor materials has always been a very popular research field. Rare earth (RE) doped ferrites are considered as potential resistive humidity sensing material owing to its high remarkable surface morphology with high porosity. Recent studies have shown that ferrite ceramics have good response in recovery time and have excellent humidity sensing behavior. With this in mind, solution combustion synthesis was used to effectively prepare RE dysprosium (Dy 3+ ) and holmium (Ho 3+ ) doped Mn–Zn ferrite ceramics with the chemical formula Mn0·5 Zn0.5 Dyx Hoy Fe2-x O4 (x = 0.005 to 0.03) (MZDHF) (where x, y = 0.0, 0.01, 0.015, 0.02, 0.025 and 0.03). The MZDHF XRD pattern revealed the purity of the samples without any secondary phase. The crystallite size MZDHF is in the nano range. Further, the calculated lattice parameter of MZDHF is found to be increasing with the RE content. The two prominent major absorption bands related to A-site and B-site were confirmed by FTIR spectra. The hysteresis loops of MZDHF are used to investigate the differences in magnetic properties with an Dy 3+ -Ho 3+ concentration. The remanence magnetization, saturation magnetization, coercivity and anisotropy of the ferrites were determined. The saturation magnetization decreases with increase of Dy 3+ -Ho 3+ concentration. The change in the surface resistance for all the samples was studied. Among all the samples, Mn0·5 Zn0.5 Dy0.03 Ho0.03 Fe1·96 O4 composite has shown a drastic variation in resistance. And the corresponding sensing response for the same sample is found to be 99%. Along with this, the sample has shown a least hysteresis and good stability. Also, the Mn0·5 Zn0.5 Dy0.03 Ho0.03 Fe1·96 O4 composite has shown a good timing behavior of 90 s and 18 s. The sensing mechanism for the prepared Mn0·5 Zn0.5 Dy0.03 Ho0.03 Fe1·96 O4 composite was thoroughly discussed.